Preoperative sedentary behavior is neither a risk factor for perioperative neurocognitive disorders nor associated with an increase in peripheral inflammation, a prospective observational cohort study - Saxena, Sarah (BMC Anesthesiol, 2020)
BACKGROUND: Surgical interventions result in a postoperative rise in circulating inflammatory cytokines and high molecular group box protein 1 (HMGB1). Herein, the impact of a sedentary lifestyle and other age-related factors on the development of perioperative neurocognitive disorders (PND) following non-cardiac surgical procedures was assessed in an older (55–75 years-old) surgical population. METHODS: Prior to surgery, patients were asked questions regarding their sedentary behavior and daily habits. They also passed the Mini Mental State Examination (MMSE) and their blood circulating interleukin 6 (IL-6) and HMGB1 levels were assayed by ELISA. IL-6 and HMGB1 measurements were repeated respectively 6 and 24 h after surgery. MMSE was re-evaluated 6 weeks and whenever possible 3 months after surgery. RESULTS: Thirty-eight patients were enrolled in the study from January until July 2019. The study identified self-sufficiency, multilinguism, and overall health score on the geriatric depression scale, as protectors against PND. No other demographic (age, sex), environmental (solitary/non-solitary housing, professional and physical activities, smoking, alcohol drinking), comorbidity (antipsychotic drug uptake, diabetic state) and type of surgery (orthopedic, general, genitourinary) influenced the development of PND. Although some factors (surgery type and age) influenced the surgery-induced rise in the circulating IL-6 levels, they did not impact HMGB1. CONCLUSION: Inflammaging, reflected by the greater increment of surgery-induced IL-6 in patients with advanced age, was present. As trauma-induced release of HMGB1 was not similarly affected by age, we surmise that HMGB1, rather than circulating cytokines, is the key driver of the trauma-induced inflammatory cascade leading to PND. TRIAL REGISTRATION: Clinicaltrials.gov identifier: NCT03805685.